RADICULAR-THE ROOT END CYST – A CASE REPORT - Dr. K. Balasankari; Dr. R.Nandhitha; Dr. S.Naveena; Dr. L.Nethradevi; Dr. Mary Tresa Jeyapriya; Dr. M. Sathish Kumar (Journal of Population Therapeutics and Clinical Pharmacology, 2023)
Large maxillary radicular cysts pose a clinical problem since they can lead to severe alveolar bone loss, disturbance of the nasal and maxillary sinus floors, and recurrent infections. We are presenting a case of a 19-year-old female patient who reported to Oral and Maxillofacial Pathology Department with a complaint of swelling in upper front tooth region for past two weeks. Radiographically, the classical findings of the lesion is a round or oval, well-defined radiolucent image involving the apex of the tooth. Upon thorough investigations, the diagnosis of radicular cyst was confirmed by histopathological findings. The treatment of choice for this case was enucleation following the extraction of the attached tooth